Reporting the whole story: Analysis of the 'out‐of‐scope' questions from the James Lind Alliance Teenage and Young Adult Cancer Priority Setting Partnership Survey. (10th July 2021) - Gibson, Faith; Fern, Lorna A.; Phillips, Bob; Gravestock, Helen; Malik, Sonia; Callaghan, Amy; Dyker, Karen; Groszmann, Mike; Hamrang, Leila; Hough, Rachael; McGeachy, Demi; Morgan, Sue; et al.
Abstract: Objective: We conducted a UK‐wide survey to identify the top 10 research questions for young people's cancer. We conducted secondary analysis of questions submitted, which were 'out‐of‐scope' of the original survey aim. We sought to disseminate these questions, to inform practice, policy and the development of potential interventions to support young people with cancer. Design: James Lind Alliance Priority Setting Partnership. Participants: Young people aged 13‐24 with a current/previous cancer diagnosis, their families/friends/partners and professionals who work with this population. Methods: Eight hundred and fifty‐five potential research questions were submitted, and 326 were classified as 'out‐of‐scope'. These questions, along with 49 'free‐text' comments, were analysed using thematic analysis. Results: The 375 out‐of‐scope questions and comments were submitted by: 68 young people, 81 family members/partners/friends and 42 professionals. Ten overarching themes were identified: diagnostic experience; communication; coordination of care; information needs and lack of information; service provision; long‐term effects and aftercare support; family support; financial impact; end‐of life care; and research methods and current research. Conclusions: The need to tailor services, information and communication is a striking thread evidenced across the 'out‐of‐scope' questions. Gaps in information highlight implications for practice in revisiting information needs throughout the cancer trajectory. We must advocate for specialist care for young people and promote the research priorities and these findings to funding bodies, charities, young people and health and social care policymakers, in order to generate an evidence base to inform effective interventions across the cancer trajectory and improve outcomes. Patient/public contributions: Patients and carers were equal stakeholders throughout.